Reduced Water Use in Barley and Maize Production Through Conservation Agriculture and Drip Irrigation - Fonteyne, Simon; Flores García, Álvaro; Verhulst, Nele (Frontiers in Sustainable Food Systems, 2021)
The Mexican Bajío region is the country's main barley (Hordeum vulgare) producing area. Barley is commonly produced during the dry autumn–winter season using furrow irrigation with ground water, following which rainfed maize (Zea mays) is grown in the spring–summer season using supplementary irrigation. Ground water levels in the region are steadily dropping, and the introduction of water-saving technologies in agriculture is urgently required. Drip irrigation can reduce water use but is costly. Conservation agriculture—the combination of minimal tillage, permanent soil cover and crop diversification—might reduce water use, but studies in irrigated systems are scarce. We compared water use and grain yield in tillage-based conventional agriculture and conservation agriculture, both with furrow irrigation and drip irrigation, in a 3-year (six growing seasons) barley-maize field experiment. Additionally, side-by-side demonstrations of conventional and conservation agriculture were installed simultaneously in farmers' fields and yields, water use and fuel use were recorded. In the field experiment, yields did not differ significantly between production systems, but irrigation water use was on average 17% lower in conservation agriculture than in conventional agriculture, 36% lower with drip irrigation compared with furrow irrigation in conventional tillage, and 40% lower with drip irrigation and conservation agriculture combined compared with conventional agriculture with furrow irrigation. Water use reductions differed strongly between years, depending on weather. The water saving through conservation agriculture in farmers' fields was similar to the water saving in the controlled experiment with about 17%. Additionally, in farmer's fields conservation agriculture reduced greenhouse gas emissions by 192 kg CO2 ha−1 and improved soil health. The implementation of conservation agriculture would be a cost-effective method to reduce water use in the barley-maize production system in the Mexican Bajío, while simultaneously reducing greenhouse gas emissions.